Comment on "kinetic simulations of magnetized turbulence in astrophysical plasmas" - Matthaeus, W. H. (2008)
A Comment on the Letter by G.G. Howes, Phys. Rev. Lett.PRLTAO0031-9007 100, 065004 (2008)10.1103/PhysRevLett.100.065004. The authors of the Letter offer a Reply. © 2008 The American Physical Society.